Near real-time surveillance of safety outcomes in US COVID-19 vaccine recipients aged 12 to 64 years. Issue 45 (26th October 2022) - Lloyd, Patricia C.; Hu, Mao; Wong, Hui-Lee; Shoaibi, Azadeh; Ke Zhou, Cindy; Lo, An-Chi; Amend, Kandace; Beachler, Daniel C.; McMahill-Walraven, Cheryl N.; Smith, Elizabeth R.; Seeger, John; Secora, Alex; et al.
Abstract: Background: Active monitoring of safety outcomes following COVID-19 vaccination is critical to understand vaccine safety and can provide early detection of rare outcomes not identified in pre-licensure trials. We present findings from an early warning rapid surveillance system in three large commercial insurance databases including more than 16 million vaccinated individuals. Methods: We evaluated 17 outcomes of interest following COVID-19 vaccination among individuals aged 12–64 years in Optum, HealthCore, and CVS Health databases from December 11, 2020, through January 22, 2022, January 7, 2022, and December 31, 2021, respectively. We conducted biweekly or monthly sequential testing and generated rate ratios (RR) of observed outcome rates compared to historical (or expected) rates prior to COVID-19 vaccination. Findings: Among 17 outcomes evaluated, 15 did not meet the threshold for statistical signal in any of the three databases. Myocarditis/pericarditis met the statistical threshold for a signal following BNT162b2 in two of three databases (RRs: 1.83–2.47). Anaphylaxis met the statistical threshold for a signal in all three databases following BNT162b2 vaccination (RRs: 4.48–10.86) and mRNA-1273 vaccination (RRs: 7.64–12.40). Discussion: Consistent with published literature, our near-real time monitoring of 17 adverse outcomes following COVID-19 vaccinations identified signals for myocarditis/pericarditis and anaphylaxis following mRNA COVID-19 vaccinations. The method is intended for early detection of safety signals, and results do not imply a causal effect. Results of this study should be interpreted in the context of the method's utility and limitations, and the validity of detected signals must be evaluated in fully adjusted epidemiologic studies.